Optimizing the use of cesarean section in Argentina: design and methodology of a formative research for the development of interventions - Ramos, Silvina (2021)
Fil: Ramos, Silvina. CEDES. Centro de Estudio de Estado y Sociedad. Área de Salud, Economía y Sociedad; Argentina.